1994
DOI: 10.1086/174589
|View full text |Cite
|
Sign up to set email alerts
|

Compact radio cores in Seyfert galaxies

Abstract: We have observed a sample of 157 Seyfert galaxies with a 275 km baseline radio interferometer to search for compact, high brightness temperature radio emission from the active nucleus. We obtain the surprising result that compact radio cores are much more common in Seyfert 2 than in Seyfert 1 galaxies, which at first seems to be inconsistent with orientation unification schemes. We propose a model, involving optical depth effects in the narrow-line region, which can reconcile our result with the standard unifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 43 publications
7
62
5
Order By: Relevance
“…Our large number of detections is also unusual for Seyfert galaxies selected in the optical or infrared. Roy et al (1994) observed samples of Seyfert galaxies with similar spatial resolution to our VLBI snapshots and detected compact radio cores in $38%.…”
Section: Morphologg Iessupporting
confidence: 64%
“…Our large number of detections is also unusual for Seyfert galaxies selected in the optical or infrared. Roy et al (1994) observed samples of Seyfert galaxies with similar spatial resolution to our VLBI snapshots and detected compact radio cores in $38%.…”
Section: Morphologg Iessupporting
confidence: 64%
“…dyn (KSR) to ensure a statistical connection between the two scales. Roy et al (1998) found that Seyfert galaxies with bright compact radio cores, independent of the presence of any larger scale outflow, also deviate significantly from the far-infrared-radio correlation. They pointed out that the compact radio source alone does not suffice to explain the radio excess, but that there must be significant radio emission on scales larger than 0B1, the detection limit of the interferometer.…”
Section: Ksrs Originate From Nuclear Jetsmentioning
confidence: 86%
“…A study by Roy et al (1994) shows that compact cores are more common in Seyfert 2 galaxies (46%) than in Seyfert 1 galaxies (26%). Increasing the free-free absorption optical depths in the Narrow Line Region may account for the different detection rates within a unified AGN model.…”
Section: Evaluation Of the Radio Classificationmentioning
confidence: 99%